Game-based training in critical infrastructure protection and resilience. (August 2022) - Galbusera, Luca; Cardarilli, Monica; Gómez Lara, Marina; Giannopoulos, Georgios
Abstract: Several institutions worldwide are reflecting on the relevance of training and exercises to critical infrastructure protection and resilience. This is witnessed, for instance, by Council Directive 2008/114/EC in the EU and the Homeland Security Exercise and Evaluation Program in the US. Contributing to the research actions in the field, the present article discusses methodological approaches, tools, techniques, and technologies relevant to this domain. In particular, we report on a recent training initiative elaborated by the authors and involving a game-based, modelling-and-simulation-backed, computer-assisted exercise for critical infrastructure expert audiences. This was developed taking advantage of JRC's Geospatial Risk and Resilience Assessment Platform (GRRASP) and critical infrastructure analysis methodologies integrated therein. The overarching objective was to enhance system thinking and raise awareness of resilience aspects while familiarizing participants with specific analysis tools and scientific models.